Pembuatan Website Desa Sebagai Media Informasi dan Pengenalan Potensi Desa Watuagung Kecamatan Prigen Kabupaten Pasuruan - Zendhi Yuna Burnama; Afrizal Nurdiansyah; Arief Wicaksono (CV. ITTC INDONESIA, 2024)
A village website is a site that contains several collections of information in the form of writing, images and videos which can be accessed via a network such as the Internet via an Internet address known as a URL. A village website is very important for a village because it aims to publicize the existence of Watuagung Village so that it can be known. by all Indonesian people and even the world. And it also functions as a means for the people of Desa Watuagung to get information quickly without obstacles which can be easily accessed by all village residents and even throughout Indonesia. However, several villages still do not have adequate website platform facilities to connect information between residents and promote local potential, one of which is Desa Watuagung. This is because most of the Desa Watuagung officials do not fully understand the use and management of websites and the information technology facilities in the village do not support it in terms of human resources or infrastructure. As a solution, a Village Website was developed with the aim of introducing Desa Watuagung and its potential. The method used is to develop a website and then fill it with content containing the profile and potential of Desa Watuagung.